Analisis Paritas Daya Beli Pada Kurs Rupiah terhadap Dolar Amerika Serikat Periode September 1997 – Desember 2007 dengan Menggunakan Metode Error Correction Model - Grisvia Agustin (Universitas Negeri Malang, 2009)
Purchasing Power Parity theory is the one of exchange rate determination theory that commonly been tested its validity. This theory explains relationship among relative inflation rate with international currency exchange rate. This research uses error correction model to test the validity of theory on rupiah exchange rate to American dollar on the floating exchange rate system. Data to be analyzed are monthly data from September 1997 to December 2007. Analysis result proves the validity of PPP theory in Indonesia. It is urging to maintain the price stability that reflects inflation. The difference of price level can exacerbate exchange rate in the short term as well as in the long term.Keywords: purchasing power parity, floating exchange rate system, error correction model_________________________________________________________________________________